Komunikasi Pemasaran Avvesome Project melalui Media Sosial Tiktok - Safiranadya Fithri Sungkar; M. Subur Drajat (Bandung Conference Series: Public Relations, 2022)
Abstract. Avvesome Project is an individual business engaged in photography services. In developing its business, Avvesome Project which was established and managed by Rivan Rahapurna conducted its business marketing through social media, so that with the current emergency “PPKM” Java-Bali there is no reason to hinder the development of its business. The social media that will be discussed in this study is TikTok. The amount of enthusiasm from TikTok users towards interesting content about the Avvesome Project presented by Rivan through his personal account @rivanrahapurna makes researchers interested in knowing the marketing communication conducted by Rivan with qualitative methods using phenomenological study approach and interactionist paradigm. The purpose of this research is 1) To find out the motive of Avvesome Project marketing communication through TikTok social media on @rivanrahapurna account in the middle of the emergency “PPKM” Java-Bali. 2) To find out the Avvesome Project marketing communication experience through TikTok sosial media on @rivanrahapurna in the middle of emergency “PPKM” Java-Bali, and 3) To find out the meaning of Avvesome Project marketing communication through TikTok social media on @rivanrahapurna account in the middle of emergency “PPKM” Java-Bali. In this research, the theory used is symbolic interaction theory which is fundamental to Marketing Communication and Social Media theory. The research subject of this study is Rivan Rahapurna, as the founder and manager of the Avvesome Project. The data will be collected through observation, in-depth interviews, and documentation which were then analyzed and was tested for validity through source triangulation and method triangulation. The results of this study concluded that with high consistency, Rivan was able to find his identity, to provide employment opportunities for workers in need. Rivan interprets this as a form of worship. Abstrak. Avvesome Project adalah sebuah bisnis perorangan yang bergerak pada bidang jasa fotografi. Dalam mengembangkan bisnisnya, Avvesome Project yang didirikan dan dikelola oleh Rivan Rahapurna melakukan pemasaran bisnisnya melalui media sosial, sehingga dengan adanya PPKM darurat Jawa-Bali saat ini tidak menjadi alasan untuk menghambat perkembangan bisnisnya. Media sosial yang akan dibahas pada penelitian ini adalah TikTok. Banyaknya antusias masyarakat terhadap konten TikTok Avvesome Project yang dibawakan oleh Rivan melalui akun pribadinya @rivanrahapurna membuat peneliti tertarik untuk mengetahui komunikasi pemasaran yang dilakukan oleh Rivan dengan metode kualitatif menggunakan pendekatan studi fenomenologi dan paradigma interaksionis. Tujuan dari penelitian ini yaitu 1) Untuk mengetahui motif komunikasi pemasaran Avvesome Project melalui media sosial TikTok pada akun @rivanrahapurna di tengah PPKM darurat Jawa-Bali. 2) Untuk mengetahui pengalaman komunikasi pemasaran Avvesome Project melalui media sosial TikTok pada akun @rivanrahapurna di tengah PPKM darurat Jawa-Bali, dan 3) Untuk mengetahui makna komunikasi pemasaran Avvesome Project melalui media sosial TikTok pada akun @rivanrahapurna di tengah PPKM darurat Jawa-Bali. Dalam penelitian ini, teori yang digunakan adalah komunikasi pemasaran dan media sosial yang mendasar pada teori interaksi simbolik. Subjek dari penelitian ini adalah Rivan Rahapurna sendiri selaku pendiri sekaligus pengelola dari Avvesome Project. Data dikumpulkan dari Teknik observasi, wawancara mendalam, dan dokumentasi yang kemudian dianalisis dan diuji keabsahannya melalui triangulasi sumber dan triangulasi metode. Hasil penelitian ini disimpulkan bahwa dengan konsistensi yang tinggi, Rivan dapat menemukan jati dirinya, sampai menyediakan lapangan pekerjaan bagi tenaga kerja yang membutuhkan. Rivan memaknai hal tersebut sebagai suatu bentuk dari ibadah.